The effects of antitakeover provisions on acquisition targets - Sokolyk, Tatyana (Journal of Corporate Finance, 2011)
This study provides large sample evidence on the effects of antitakeover provisions (ATPs) on takeover probability and premia in modern takeover contests. Despite the fact that hostile bids are uncommon during the 1990s–2000s, some ATPs have strong but opposing effects on takeover outcomes. Consistent with recent theory, the staggered board-poison pill combination is the strongest antitakeover mechanism. Takeover compensation arrangements reduce managerial resistance to takeovers, and many commonly used ATPs are irrelevant in modern takeover battles. Furthermore, compensation plans are associated with higher takeover premia. Although individual ATPs have significant effects on takeover outcomes, the G-Index, which does not account for the diverse effects of ATPs, is not significant in predicting the firm's takeover probability or the size of takeover premia.